2010
DOI: 10.1007/s11199-010-9835-x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Underrepresentation: A Theory of Precluded Interest

Abstract: What processes best explain women’s underrepresentation in science, math, and engineering fields in the U.S.? Do they also explain men’s underrepresentation in the humanities? Two survey studies across two U.S. West Coast universities (N = 62; N = 614) addressed these questions in the context of two fields: one male-dominated (computer science) and the other female-dominated (English). Among a set of social predictors—including perceived similarity to the people in the field, social identity threats, and expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(158 citation statements)
references
References 107 publications
3
151
0
4
Order By: Relevance
“…Openness for research is more visible among male than female students (see also Blickenstaff, 2005;Kamphuis, 2007;Cheryan & Plaut, 2010). Our data also confirm a statement made by Duffy and Sedlacek (2007): women score 4.06 out of 5 on the question 'In my future job I would like to mainly work with people', whereas male students score an average 3.65 out of 5, which is significantly lower (p< .0001).…”
Section: Journal Of Education and Trainingsupporting
confidence: 82%
See 2 more Smart Citations
“…Openness for research is more visible among male than female students (see also Blickenstaff, 2005;Kamphuis, 2007;Cheryan & Plaut, 2010). Our data also confirm a statement made by Duffy and Sedlacek (2007): women score 4.06 out of 5 on the question 'In my future job I would like to mainly work with people', whereas male students score an average 3.65 out of 5, which is significantly lower (p< .0001).…”
Section: Journal Of Education and Trainingsupporting
confidence: 82%
“…Educational aspirations is defined as progression on the different levels of higher education. The higher preference of male students for a research career in comparison with female students finds confirmation by Blickenstaff (2005), Kamphuis (2007), and Cheryan and Plaut (2010). This is not confirmed by Zafira (2012) for students choosing for graduate school: "controlling for ability, aspirations, and confidence" the gender difference is no longer significant.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, if an environmental cue suggests that an individual's social identity is negatively valued in a domain, it can cause social identity threat, including stereotype threat, where vigilance is raised and performance may suffer (see (Inzlicht and Schmader 2012;Major and O'Brien 2005;Spencer et al 2016), for reviews). Social identity threat includes the fear of becoming negatively stereotyped and discriminated in a domain (Cheryan and Plaut 2010;Murphy et al 2007;Petriglieri 2011;Steele et al 2002) and may diminish a person's sense of control (Chithambo et al 2014;Fischer and Bolton Holz 2010). Previous research has shown that contexts dominated by men can trigger social identity threat in women (Inzlicht and Ben-Zeev 2000;Major and O'Brien 2005;Murphy et al 2007;Sekaquaptewa et al 2007;Steele et al 2002).…”
Section: Social Identity Threats and Identity Safetymentioning
confidence: 99%
“…Social identity threat tends to be unrelated to interests in a domain (e.g., Cheryan and Plaut 2010). However, repeated exposure to social identity threat can push people to withdraw from a career path, despite interest in it (Thoman et al 2013;Woodcock et al 2012).…”
Section: Interest and Self-efficacymentioning
confidence: 99%